2018
DOI: 10.1038/s41586-018-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the adenosine-bound human adenosine A1 receptor–Gi complex

Abstract: The class A adenosine A receptor (AR) is a G-protein-coupled receptor that preferentially couples to inhibitory G heterotrimeric G proteins, has been implicated in numerous diseases, yet remains poorly targeted. Here we report the 3.6 Å structure of the human AR in complex with adenosine and heterotrimeric G protein determined by Volta phase plate cryo-electron microscopy. Compared to inactive AR, there is contraction at the extracellular surface in the orthosteric binding site mediated via movement of transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
332
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(372 citation statements)
references
References 55 publications
22
332
1
Order By: Relevance
“…Residue positions in this barcode represent the determinants of GPCR‐G protein selectivity, as deduced from evolutionary conservation (conserved in orthologs but not in paralogs) (36). Given the limited structural coverage of receptors and complexes to model a GPR35‐Gα 13 complex, we looked at the currently available receptor–G protein complexes of µ‐opioid receptor–Gα i1 (45), β 2 ‐adrenoceptor‐Gα s (8), adenosine A 1 receptor‐Gα i2 (46), and 5‐HT 1A –Gα o1 (47) to attempt to rationalize the importance of G.H5.23 for G 13 function. A comparison between these structures reveals differences in the position of transmembrane receptor helix VI and in the orientation between the G protein's α5 helix domain (∼20° rotation) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residue positions in this barcode represent the determinants of GPCR‐G protein selectivity, as deduced from evolutionary conservation (conserved in orthologs but not in paralogs) (36). Given the limited structural coverage of receptors and complexes to model a GPR35‐Gα 13 complex, we looked at the currently available receptor–G protein complexes of µ‐opioid receptor–Gα i1 (45), β 2 ‐adrenoceptor‐Gα s (8), adenosine A 1 receptor‐Gα i2 (46), and 5‐HT 1A –Gα o1 (47) to attempt to rationalize the importance of G.H5.23 for G 13 function. A comparison between these structures reveals differences in the position of transmembrane receptor helix VI and in the orientation between the G protein's α5 helix domain (∼20° rotation) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although GPCR and cognate G protein structure determination is advancing rapidly (8,(45)(46)(47), there are little direct data on how much difference might be expected for a receptor in complex with 2 different G proteins. Van Eps et al (50) have suggested differences in the ways in which 2 distinct GPCRs interact with their cognate G proteins, but the outcomes are predictions rather than direct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The first two cryo‐EM GPCR complex structures were determined for glucagon‐like peptide 1 receptor (GLP1R) and calcitonin receptor (CTR), both in complex with the stimulatory Gs protein . Entering 2018, a cryo‐EM structure of rhodopsin in complex with Gi, a homologue of the G protein transducin, and three other structures, μ‐opioid receptor (μOR) –Gi complex, adenosine A 1 receptor (A 1 R)‐Gi complex, and serotonin 5‐HT 1b R in complex with Go, have been reported . Most recently, a crystal structure of bovine rhodopsin in complex with a mini‐Go that includes the Ras domain of Gαo subunit, was published …”
Section: Introductionmentioning
confidence: 99%
“…The four papers in this issue report structures of G i/o -bound GPCRs obtained using cryoelectron microscopy: Koehl et al 2 (page 547) report the structure of the µ-opioid receptor bound to G i1 ; Draper-Joyce et al 3 (page 559) describe the adenosine A 1 receptor in complex with G i2 ; García-Nafría et al 4 (page 620) report the 5HT 1B receptor bound to G o ; and Kang et al 5 (page 553) reveal the structure of the light receptor rhodopsin in complex with G i1 . The G-protein activation cycle involves the binding and release of nucleotides to and from the G proteins, and all of the reported structures capture the receptors bound to the nucleotidefree state of their respective G proteins.…”
mentioning
confidence: 99%
“…GPCRs span the cell membrane and convert myriad extra cellular signals, including neurotransmitter molecules, hormones, and even light, into a cellular response by activating cellular G proteins and other transducer proteins. Four papers [2][3][4][5] in this issue help to unravel the mystery of how GPCRs selectively activate a particular group of G proteins known as G i/o , and provide clues that might aid the design of improved GPCR-targeting drugs.…”
mentioning
confidence: 99%